The usage of Jati Leaves Extract (Tectona grandis L.f) As color of lipstick - Rety Setyawaty; Meldina R. Pratama (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Lipstick is one of the most used cosmetics by women. According to Tranggano and Latifah (2007), lipstick is a cosmetic applied to the lips, to protect the lips in cold and dry air so that the lips are not easy to dry and crack. Lipstick is used by women for a long time so that lipstick should be safe and do not cause irritation. Chemicals substances in the manufacture of lipstick can accidentally be consumed and long-term use so that its accumulation in the body would be harmful to health. Synthetic lipstick color is one part of the dangerous lipstick making material. Synthetic substances can be replaced with natural dyes. The use of natural dye limits on cosmetics is 5-15% (Mercado, 1991). One example of natural dyes that can be used is the dye from the Jati leaves (Tectona grandis L.f). This study aim is to prove that Jati leaves (Tectona grandis L.f) can be used as a natural dye in the material of lipstick. The method used in this research is the method of extraction maceration with jati leaf samples of 300 grams and ethanol of 96%. Component of lipstick formula which are cera alba, lanolin, vaseline, cetyl alcohol, paraffin solid, oleum ricini, oleum rosae, propylene glycol, butyl hydroxytoluene, methyl paraben, and the addition Jati leaf extract under the concentration of 0%, 18% , and 22%. The material of lipstick is easy to apply, stable, brown color, homogeneous, melting point of 600C, range pH between 3 at 4 and lipstick have a breaking point of 500 grams. Jati leaf extract (Tectona grandis L.f) can be used as a dye or color of lipstick.